Communication Ethics: Focus on Communication Professionals. - Lucas, Richard (Spring;Communication., 1999)
Keywords: dept.com; faculty_collection; sabbatical_report

Interpersonal conflict from a younger point of view: Exploring the perspectives of children - Hale, C.L.; Farley-Lucas, B.; Tardy, R.W. (International Journal of Qualitative Studies in Education, 1996)
This study breaks from traditional adult-centered models of interpersonal conflict by privileging children’s experiences. As part of an assessment for establishing a school-based peer mediation program, focus group interviews were conducted with second graders through high school students. Analysis focuses on the sites (causes), signs, and aftermath (or responses) of conflict. Children’s impressions regarding fairness and gender differences are also addressed. With respect to the sites and signs of conflict, the main themes that were found include conflict as a product of the spoken word and conflict as a dirty look. Additionally, a symbolic representation of these intrusions emerged in the metaphor of conflict as an explosion. Analysis of the children's discussions concerning the aftermath of conflicts revealed four general themes: confronting, seeking involvement of third parties, ignoring others, and treating others with kindness. Differences in the children’s perceptions of gender-based differences are explored as are their perceptions of the construct of “fairness” and its associated dictates in favor of equality of treatment, struggles with inferiority/superiority, and expression of conflict as a betrayal. © 1996, Taylor & Francis Group, LLC. All rights reserved.
Keywords: dept.com

A second look at thorstein veblen the aesthetics of thorstein veblen revisited - Tilman, R.; Griffin, R. (Cultural Dynamics, 1998)
The aesthetics of Thorstein Veblen (1857-1929) have been evaluated by aestheticians and social scientists of various ideological persuasions. Because of Veblen's stature as an American critical theorist and the debate which has ensued over the nature of his aesthetics, further efforts to both clarify and extrapolate from them are self-justificatory. The focus here is on (1) Veblen's view of aesthetic experience, (2) the nature of the non-invidiously beautiful in his aesthetics, (3) his distinction between pure and applied art forms and its importance to the common person and (4) the social basis and artistic consequences of the non-invidious as exemplified in the painting of the American artist Winslow Homer (1836-1910). Problematic areas in Veblen's social theory and aesthetics are addressed and a non-invidious aesthetic of countervailence articulated using Homer's work. Copyright © 1998 SAGE Publications.
Keywords: Aesthetic countervailence economics non-invidious aesthetics; dept.com

Children's talk about conflict: an exploration of the voices and views of the `Experts': - Hale, Claudia L.; Tardy, Rebecca W.; Farley-Lucas, Bonnie (Discourse & Society, 1995)
The research reported in this paper is an exploration of children's understandings of the concept and experience of interpersonal conflict. Data were gathered at focus group discussions with 7- to 16-year-old children. The analysis which is presented focuses on the children's metaphors of conflict as a place, conflict as an explosion and conflict as betrayal. Children's own descriptions of their experiences and understandings are emphasized. Thus, to the extent possible, what is presented is an examination of children's perspectives/voices as opposed to adult-centered analyses of children's experiences.
Keywords: betrayal; children's discourse; conflict; dept.com; explosion; fighting; interpersonal conflict; metaphors; place